ChemInform Abstract: New 2‐Benzoxazolinone Derivatives with Cytotoxic Activities from the Roots of Acanthus ilicifolius. Issue 16 (March 2016) - Zhao, Dan; Xie, Lijun; Yu, Lei; An, Ni; Na, Wei; Chen, Feng; Li, Youbin; Tan, Yinfeng; Zhang, Xiaopo
Abstract: Four new 2‐benzoxazolinone‐type alkaloids, acanthosides A—D, are isolated along with three known ones.